Fiscal policy and direct democracy: institutional design determines outcomes - Feld, Lars P.; Kirchgässner, Gebhard (The Elgar companion to public economics, 2006)
"Chapter 13: Fiscal Policy and Direct Democracy: Institutional Design Determines Outcomes" published on 26 Apr 2006 by Edward Elgar Publishing.
Gesehen am 28.09.2022